2022-RA-1417-ESGO Evaluation of the gynaecology oncology surgeries complications at UHL. (20th October 2022) - Abdelrasol, Mostafa; Barakat, Anas; Polymeros, Kostantinos; Chattopadhyay, Supratik; Davies, Quentin; Ismail, Aemn
Abstract : Introduction/Background: University Hospital of Leicester (UHL) is a tertiary center for gynaecology oncology, we aim to evaluate the complication rates across different operative modalities that was performed by the gynaecology oncology surgeons at UHL. This information is important for patient counselling. Methodology: We identified all major gynaecology oncology cases performed at our tertiary centre in 2021, Cases were assessed for operation type, diagnosis and co-morbidities. Complications then assessed using Clavien-Dindo classification. Data about complications obtained from Electronic Discharge Notes and follow up clinic letters. Standard used was the UK Gynaecological Oncology Surgical Outcomes and Complications audit of 25.9% on inclusion of all patient-reported complications. Results: A total of 363 operations were identified with a rate of minor complications (Clavien-Dindo 1, 2) of 18% and the rate of major complications (Clavien-Dindo 3, 4) was one case had left ureteric injury 0.003%. 8 cases had (0.022%) intra-operative complications were described as follows: 2 bladder injuries, 1 ureteric injury, 5 bowel injuries. 2 (0.006%) deaths were recorded within 28 days of the operation (one due to COVID 19 infection and another death related to lung metastasis). No return to theatre cases were observed. Conclusion: Our major complication rate was observed to be below the national average, which is a good reflection of expertise and the value of the super specialization within our department. This results are helpful when consenting patients for procedures, as it gives knowledge on the true numbers at the local level.